Arsenic Mobilization by Citrate and Malate from a Red Mud–Treated Contaminated Soil. Issue 3 (1st May 2013) - Castaldi, Paola; Silvetti, Margherita; Mele, Elena; Garau, Giovanni; Deiana, Salvatore
Abstract : The mobility and bioavailability of As in the soil–plant system can be affected by a number of organic acids that originate from the activity of plants and microorganisms. In this study we evaluated the ability of citrate and malate anions to mobilize As in a polluted subacidic soil (UP soil) treated with red mud (RM soil). Both anions promoted the mobilization of As from UP and RM soils, with citrate being more effective than malate. The RM treatment induced a greater mobility of As. The amounts of As released in RM and UP soils treated with 3.0 mmol L −1 citric acid solution were 2.78 and 1.83 μmol g −1 respectively, whereas an amount equal to 1.73 and 1.06 μmol g −1 was found after the treatment with a 3.0 mmol L −1 malic acid solution. The release of As in both soils increased with increasing concentration of organic acids, and the co‐release of Al and Fe in solution also increased. The sequential extraction showed that Fe/Al (oxi)hydroxides in RM were the main phases involved in As binding in RM soil. Two possible mechanisms could be responsible for As solubilization: (i) competition of the organic anions for As adsorption sites and (ii) partial dissolution of the adsorbents (e.g., dissolution of iron and aluminum oxi‐hydroxides) induced by citrate or malate and formation of complexes between dissolved Fe and Al and organic anions. This is the first report on the effect of malate and citrate on the As mobility in a polluted soil treated with RM.